Business perceptions, fiscal policy and growth - Florian Misch; Norman Gemmell; Richard Kneller (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2008)
This paper develops endogenous growth models in which the government uses income taxation to finance different types of public services, public investment, or both. The paper then assesses the merits of business perceptions of alternative fiscalpolicy related growth constraints as guides for imperfectly informed governments. The models demonstrate that business perceptions may be misleading except when firms compare different types of public services or different types of public capital. It is also shown that the theoretical predictions regarding how firms most likely rank constraints correspond fairly well to the ranking of constraints by firms in the World Bank's Enterprise Surveys.
Keywords: E62; H21; H50; O40; 330; Economic Growth; Productive Public Spending; Imperfectly Informed Governments; Optimal Fiscal Policy; Constraints to Growth; Investment Climate Assessments; Öffentliche Finanzwirtschaft; Unvollkommene Information; Öffentliche Ausgaben; Einkommensteuer; Unternehmensplanung; Investitionsklima; Wirtschaftswachstum